JURIDICAL ANALYSIS OF THE EFFECTIVENESS OF ONLINE SINGLE SUBMISSION (OSS) IMPLEMENTATION RELATED TO LICENSE FOR ENVIRONMENTAL PROTECTION AND MANAGEMENT IN BATAM CITY (RESEARCH STUDY IN BATAM CITY INVESTMENT SERVICE INTEGRATED SERVICES (PTSP) - Indah Wijayanti, Titising; Fadlan, Fadlan; Washliaty, Laily; Siadari Parohha, Lagat (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The construction of the journal topic above is: "Juridical Analysis of the Effectiveness of Online Single Submission (OSS) Implementation Related to Licensing for Environmental Protection and Management in the City of Batam", with the formulation of the problem: How to Regulate Law, Implementation, Constraint Factors and Solutions to Juridical Effectiveness of Online Single Implementation Submission (OSS) Related to Licensing for Environmental Protection and Management in the City of Batam?. The type of writing is normative law, using a legal research methodology, on the support of secondary data, and using a qualitative approach, and to obtain secondary data, obtained through library research. research). For grand theory using the theory of legal objectives by Gustav Radbruch of law, middle theory using the legal theory of substance of law by M. friedman and applied theory using the theory of the law of happiness (utilitarianism) by Jeremy Bentham. The results of the analysis concluded that the Effectiveness of the Implementation of Online Single Submission (OSS) aims to facilitate investment as a framework for accelerating and increasing investment and business, by applying business permits with integrity electronically.